Invisible connections : an archaeometallurgical analysis of the Bronze Age metalwork from the Egyptian Museum of the University of Leipzig - Odler, Martin, (Archaeopress Egyptology ;, 2020)
The Egyptian Museum of the University of Leipzig has the largest university collection of ancient Egyptian artefacts in Germany. This volume presents an analysis of 86 of these artefacts using a range of archaeometallurgical methods in order to provide a diachronic sample of Bronze Age Egyptian copper alloy metalwork from Dynasty 1 to Dynasty 19.